Integration of parallel metabolomics and transcriptomics reveals metabolic patterns in porcine oocytes during maturation - Gao, Ming; Chen, Minjian; Chen, Qiuzhen; Zhu, Shuai; Wang, Hengjie; Yang, Weizheng; Wang, Xi; Wang, Qiang; Gu, Ling (Frontiers in Endocrinology, 2023)
Well-controlled metabolism is the prerequisite for optimal oocyte development. To date, numerous studies have focused on the utilization of exogenous substrates by oocytes, whereas the underlying mechanism of intrinsic regulation during meiotic maturation is less characterized. Herein, we performed an integrated analysis of parallel metabolomics and transcriptomics by isolating porcine oocytes at three time points, cooperatively depicting the global picture of the metabolic patterns during maturation. In particular, we identified the novel metabolic features during porcine oocyte meiosis, such as the fall in bile acids, the active one-carbon metabolism and a progressive decline in nucleotide metabolism. Collectively, the current study not only provides a comprehensive multiple omics data resource, but also may promote the discovery of biomarkers in the prediction and improvement of oocyte quality.